2018
DOI: 10.1063/1.5046929
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the symmetry group and exact solutions of the dispersionless KP equation in n + 1 dimensions

Abstract: The Lie algebra of the symmetry group of the (n + 1)-dimensional generalization of the dispersionless Kadomtsev-Petviashvili (dKP) equation is obtained and identified as a semi-direct sum of a finite dimensional simple Lie algebra and an infinite dimensional nilpotent subalgebra. Group transformation properties of solutions under the subalgebra sl(2, R) are presented. Known explicit analytic solutions in the literature are shown to be actually group-invariant solutions corresponding to certain specific infinit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…In summary, it has been shown that for the paraboloid front initial condition (2.4), by using the ansatz (2.5), the (3+1) dimensional PDE (2.1) is reduced to a (1+1) dimensional PDE (2.11) with variable coefficients. Similar reduced equation can be obtained by applying to the similarity reduction approaches of PDEs [28]. to Eq.…”
Section: Reduction Of 3dbo Equation To Sbo Equationmentioning
confidence: 99%
“…In summary, it has been shown that for the paraboloid front initial condition (2.4), by using the ansatz (2.5), the (3+1) dimensional PDE (2.1) is reduced to a (1+1) dimensional PDE (2.11) with variable coefficients. Similar reduced equation can be obtained by applying to the similarity reduction approaches of PDEs [28]. to Eq.…”
Section: Reduction Of 3dbo Equation To Sbo Equationmentioning
confidence: 99%
“…Özet olarak, (5) çözüm formu kullanılarak, (n+1) boyutlu (1) denklemi, (4) ile verilmiş paraboloid tipi başlangıç dalga cephesi için (1+1) boyutlu değişken katsayılı bir kısmı türevli denkleme (KTD) (9) indirgenmiştir. Benzer bir indirgeme KTD'ler için benzerlik dönüşümleri kullanılarak da elde edilebilir [14].…”
Section: (N+1) Boyutlu Benjamin-ono Denklemi̇ni̇n İndi̇rgenmesi̇unclassified